Cleavage of Carboxylic Acid Moieties in Triacylglycerides During Non‐Catalytic Pyrolysis. (3rd April 2015) - Kubátová, A.; Geetla, A.; Casey, J.; Linnen, M. J.; Seames, W. S.; Smoliakova, I. P.; Kozliak, E. I.
Abstract: Noncatalytic pyrolysis of triacylglyceride (TG) oils is an attractive option for production of renewable fuels and chemicals. This process produces 20–30 wt% of C2 –C10 fatty acids due to the presence of carboxyl moieties in TG. To decipher this process' mechanism, several compositionally distinct crop oil feedstocks with varied abundances of C18 saturated and unsaturated TG carboxylic acid chains were pyrolyzed for short residence times in a laboratory‐scale continuous turbulent flow reactor. A comprehensive gas chromatographic analysis of the oxygenated products revealed the selective formation of linear saturated monocarboxylic acids (LSMCA) of less than C11 in size, with a specific homological pattern featuring peaks for C2 –C3, C7 and C9 –C10 LSMCA. The relative abundance of these size groups varied amongst the feedstocks cracked due to variations in the abundance of triunsaturated (linolenic), diunsaturated (linoleic) and monounsaturated (oleic) acids, respectively, in the original TG. We proposed a mechanism explaining the observed product speciation and homology profiles by the formation of acyloxyl biradicals as essential intermediates. High‐temperature C=C π‐bond hydrogenation with a concomitant σ‐bond cleavage yields C9 –C10 LSMCA. This new path was confirmed by pyrolysis experiments with triolein in a GC pyroprobe.